Comparative Chloroplast Genomics of Sophora Species: Evolution and Phylogenetic Relationships in the Early-Diverging Legume Subfamily Papilionoideae (Fabaceae) - Liao, Min; Gao, Xin-Fen; Zhang, Jun-Yi; Deng, Heng-Ning; Xu, Bo (Frontiers in Plant Science, 2021)
The taxonomy and evolutionary history of Sophora L., a genus with high economic and medicinal value, remain uncertain due to the absence of genetic resource (especially in China) and low polymorphism of molecular markers. Our aim was to elucidate the molecular evolution and phylogenetic relationships in chloroplast genomes of Sophora species in the early-diverging legume subfamily Papilionoideae (Fabaceae). We reported nine Sophora chloroplast genome from China using Illumina sequencing. We performed a series of analyses with previously published genomes of Sophora species to investigate their genomic characteristics, identified simple sequence repeats, large repeat sequences, tandem repeats, and highly polymorphic loci. The genomes were 152,953–158,087 bp in length, and contained 111–113 unique genes, including 76–78 protein coding, 31 tRNA, and 4 rRNA. The expansion of inverted repeat boundary of Sophora resulted in rps12 entering into the LSC region and loss of trnT-CGU gene in some species. Also, we found an approximately 23 kb inversion between trnC-GCA and trnF-GAA within the genus. In addition, we identified seven highly polymorphic loci (Pi > 0.035) suitable for inferring the phylogeny of Sophora species. Among these, three regions also co-occurred with large repeat sequences and support use of repeats as a proxy for the identification of polymorphic loci. Based on whole chloroplast genome and protein-coding sequences data-set, a well-supported phylogenetic tree of Sophora and related taxa showed that this genus is monophyletic, but sect. Disamaea and sect. Sophora, are incongruent with traditional taxonomic classifications based on fruit morphology. Our finding provides significant genetic resources to support further investigation into the phylogenetic relationship and evolution of the genus Sophora.